Corneal in vivo Confocal Microscopy for Assessment of Non-Neurological Autoimmune Diseases: A Meta-Analysis - Gu, Yuxiang; Liu, Xin; Yu, Xiaoning; Qin, Qiyu; Yu, Naiji; Ke, Weishaer; Wang, Kaijun; Chen, Min (Frontiers in Medicine, 2022)
Purpose: To evaluate the features of corneal nerve with in vivo confocal microscopy (IVCM) among patients with non-neurological autoimmune (NNAI) diseases. Methods: PubMed, Web of Science, and Cochrane Central Register of Controlled Trials were systematically searched for studies published until May 2021. The weighted mean differences (WMDs) of corneal nerve fiber length (CNFL), corneal nerve fiber density (CNFD), corneal nerve branch density (CNBD), tortuosity, reflectivity and beadings per 100 μm with a 95% confidence interval (CI) between NNAI and control group were analyzed using random effects model. Results: 37 studies involving collective totals of 1423 patients and 1059 healthy controls were ultimately included in this meta-analysis. The pooled results manifested significantly decreased CNFL (WMD: -3.94, 95% CI: -4.77 to -3.12), CNFD (WMD: -6.62, 95% CI: -8.40 to -4.85), CNBD (WMD: -9.89, 95% CI: -14.00 to -5.79) in NNAI patients. In addition, the NNAI group showed more tortuous corneal nerve (WMD: 1.19, 95% CI: 0.57 to 1.81). The comparison between NNAI patients and healthy controls in beadings per 100 μm corneal nerve length were inconsistent. No significant difference was found in the corneal nerve fiber reflectivity between NNAI and control group (WMD: -0.21, 95% CI: -0.65 to 0.24, P=0.361). Conclusions: The parameters and morphology of corneal nerves observed by IVCM proved to be different in NNAI patients from healthy controls, suggesting that IVCM may be a noninvasive technique for identification and surveillance of NNAI diseases.